PORE-SCALE MODELLING OF FLOW BOILING HEAT TRANSFER IN METAL FOAM HEAT EXCHANGER - CHIN, ADAM REDUAN (IRC, 2021)
Heat exchangers has been essential in thermal energy system. Increasing the heat transfers performance of heat exchangers has been the main focus of thermal engineering field.